2013
DOI: 10.1063/1.4807597
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst size dependent growth of Pd-catalyzed one-dimensional InAs nanostructures

Abstract: In this study, Pd was used as catalyst to grow one-dimensional InAs nanostructures on GaAs (111)B substrates in order to explore the growth mechanism and the effect of non-gold catalysts in growing epitaxial III-V nanostructures. With detailed morphological, structural, and chemical characterizations using electron microscopy, coupled with analysis of the Pd-In binary phase diagram, it was found that size of Pd nanoparticles plays a key role in determining the growth mechanism of one-dimensional InAs nanostruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 38 publications
0
28
1
Order By: Relevance
“…Nanowire growth from solid particles has previously been shown to occur by step/ledge-flow at the seed particle/nanowire interface 25,33 ; thus, it has been proposed that such an anisotropic interface induces twin-mediated kinking, responsible for the curly morphology. 34 A solid Pd-Ga seed particle may therefore explain the observed curly morphology. Although VSS growth is generally associated with lower growth rates due to the lower bulk diffusion in solids than in liquids, the absolute magnitude of the growth rate also depends on the particle material.…”
Section: Discussionmentioning
confidence: 97%
“…Nanowire growth from solid particles has previously been shown to occur by step/ledge-flow at the seed particle/nanowire interface 25,33 ; thus, it has been proposed that such an anisotropic interface induces twin-mediated kinking, responsible for the curly morphology. 34 A solid Pd-Ga seed particle may therefore explain the observed curly morphology. Although VSS growth is generally associated with lower growth rates due to the lower bulk diffusion in solids than in liquids, the absolute magnitude of the growth rate also depends on the particle material.…”
Section: Discussionmentioning
confidence: 97%
“…18 However, understanding the size-dependent growth of InAs nanowires and achieving high-quality InAs nanowires require further investigations. 19 In this letter, we investigated the structural characteristics of Au-catalyzed epitaxial InAs nanowires grown by molecular beam epitaxy (MBE). Through detailed structural and chemical characterizations using electron microscopy, it has been found that the structural quality of InAs nanowires can be well controlled by the size of Au catalysts.…”
mentioning
confidence: 99%
“…In most cases, nanowires grown along the 111 B /000 -1 directions with the {111} B /{000 -1} catalyst/nanowire interfaces tend to naturally contain uncontrolled mixture of polytypes and/ or adopt planar defects [24][25][26], such as stacking faults or twins due to the small energetic differences for the stacking consequences in zinc-blende and wurtzite structures along their 111 B /000 -1 directions [27]. To date, scientific findings have been reported that the growth of free-standing III-V nanowires are with non-111 B /000 -1 growth directions [22,[27][28][29][30][31][32][33]. It is of interest to note that most of these non-111 B /000 -1 nanowires generally have high structural quality.…”
Section: Introductionmentioning
confidence: 99%
“…To solve this issue, the epitaxial nanowire growth provides the uniqueness that well aligned nanowires can be grown on the chosen substrates, and by selecting substrates with particular orientations, specifically orientated nanowires can be grown. The epitaxial III -V semiconductor nanowires are generally grown in metal-organic chemical vapor deposition [8][9][10], molecular beam epitaxy [11][12][13], chemical vapor deposition [14,15], through the vapor-liquid-solid [16][17][18][19] or the vapor-solid-solid mechanisms [20][21][22].…”
Section: Introductionmentioning
confidence: 99%